New hosts and morphological data for the Star pearlfish Carapus mourlani (Ophidiiformes: Carapidae) from collections made in the North Pacific coast of Costa Rica - Chacón-Monge, José-Leonardo (2021)
Introduction: The family Carapidae includes about 40 species of marine fishes distributed in coastal habitats worldwide. The family includes some free-living species, however, most of them are found as commensal inquilines or parasites of marine invertebrates, including several echinoderm species. In the Eastern Tropical Pacific, the biology and host use of the representatives of the Carapidae is relatively poorly known. Objective: The present study reports the occurrence of the Star pearlfish Carapus mourlani within three previously unknown hosts in the region: the sea stars Nidorellia armata, Phataria unifascialis, and the sea cucumber Stichopus horrens. Some ecological implications and considerations regarding such symbiotic relationships are raised and discussed. Additional morphometric and meristic data for the fish and the echinoderms are also provided and discussed. Methods: Echinoderms were collected, from 25 localities along the North Pacific coast of Costa Rica, and were carefully examined searching for commensal/parasitic fishes. Echinoderms and fishes were identified and characterized in accordance with the specialized literature. Results: A total of 497 echinoderms, including about 60 species, were collected and examined. Commensal/parasitic fish (a single species represented by 13 specimens) were found in three echinoderm specimens/species. Conclusions: The list of echinoderm hosts for this carapid fish, through its whole distribution range, rises to 12 species (six sea stars and six sea cucumbers) and that could be a consequence of its wide geographic distribution, its generalist feeding habits and opportunistic commensal behavior.